ANALISIS EVA, EPS, DAN PER TERHADAP RETURN SAHAM PADA PERUSAHAAN SUB SEKTOR MAKANAN & MINUMAN - Andri Syahputra (Universitas Pamulang, 2018)
The companies of food and baverage sub-sector play a vital role in country’s economy and social life. This research aims to determine the influences of Economic Value Added (EVA), Earnings Per Share and Price to Earnings Rasio (PER) simultaneously on Stock Return. By using multiple linear regression analysis with SPSS 24.0 for Windows, the results of this research indicate that EVA, EPS, and PER simultaneously have a significant influence on Stock Return. In addition, the results of this research also show that EVA is a determinant variable in influencing Stock Return.